The Effect of Aerobic Exercises on the Visual and Auditory Attention of Pre-school Boys with ADHD in Isfahan in 2009–2010 - Ahmad Abedi; Fereshteh Kazemi; Mozhgan Shooshtari; Fereshteh Golshani Monazzah (Ravānshināsī-i Afrād-i Istis̠nāyī, 2012)
The aim of this research is to investigate the effect of aerobic exercises on improving the visual and auditory attention of children with attention-deficit/hyperactivity disorder. In this quasi-experimental study, 30 children with attention-deficit/hyperactivity disorder are selected from among the six year-old preschool children of Isfahan city via random cluster sampling method and are then randomly assigned to experimental and control groups (each group consists of 15 children). The experimental group performed aerobic exercises. The instruments used include the neuropsychological test of NEPSY, (SNAP-IV) parent rating scale and clinical interview. The gathered data are analyzed by multivariate analysis of covariance (MANCOVA). The findings indicate that aerobic exercise can improve visual and auditory attention of children with attention-deficit/hyperactivity disorder.